Vitamina D em mulhers adultas fumantes e ex-fumantes: ingestão, concentração sérica e associação com variáveis ecocardiográficas - Fidélix, Melaine Priscila [UNESP] (2014)
Smoking is a risk factor for cardiovascular diseases. Experimental and clinical studies showed that the smoke inhalation of cigarette smoke leads to functional and morphological changes in the heart and this is negatively associated with serum vitamin D concentrations. In addition, there are reports of the association between vitamin D and cardiac remodeling. Thus, the objective was to determine whether the serum concentration of vitamin D and smoking habits explain the structural and functional cardiac variables in women and ex-smokers women compared to healthy women. Methods: Cross-sectional observational study in which 55 women were evaluated, 19 never smokers (control, 44,4±11 years), 18 active smokers (52,8±7 years) and 18 ex-smokers (51,7±8 years). It was evaluated the blood pressure, sun exposure questionnaire, dietary intake (24-hour recall in triplicate), body composition (weight, height, body mass index (BMI), circumferences (arm, waist, abdominal) and hip, bone mineral density, fat mass and fat-free mass X-ray absorptiometry dual energy absorptiometry (DXA)), laboratory analysis (serum calcium, total cholesterol and fractions, triglycerides, creatinine, urea, glucose, glycated hemoglobin, C-reactive protein, total proteins and fractions, parathyroid hormone (PTH), vitamina D (25(OH)D) and blood test), echocardiogram and spirometry. The results were analyzed using descriptive statistical tests, group comparisons, proportions, correlations and multiple linear regression, with significance level of 5%. Results: In three groups, BMI classification was overweight and values of waist circumference and waist/hip higher than the cutoffs for healthy women in all groups were observed. There was no difference between body composition variables. The concentrations of total and LDL cholesterol were higher in the group ex-smoker. Dietary intake of vitamin D and calcium was lower than those recommende by the EAR ...